Analysis on Students’ Interrogative Sentence Error at SMA Negeri 2 Samalantan Bengkayang Regency - Magpika Handayani; Yovita Angelina (JETL (Journal of Education, Teaching and Learning), 2019)
This study aims at identifying the form of questions used by students of SMA Negeri 2 Samalantan Bengkayang Regency, sees errors done by students and describes students' understanding of English interrogative sentence patterns. The location of the research was conducted at SMA Negeri 2 Samalantan Bengkayang Regency because this school is one of the schools that implement the mandatory system of using English in English subjects. In fulfilling these obligations, students often find difficulty in asking in English. The study of interrogative sentences in the students of SMA Negeri 2 Samalantan Bengkayang Regency is a way to solve the problems of students in making interrogative sentences so that learning English activities become easier and students can ask each other questions with correct questions sentence pattern. The method used in this study is describing students' understanding of the interrogative sentences obtained through a list of questions in the form of translation and interviews to determine the form of errors in making questions. The data obtained is then analyzed to obtain the results of research on the difficulties faced by students in understanding the interrogative sentences. The results of this study show the most dominant error in the sentence Yes/No verbs, then Wh-question noun, Wh-type verb type, and the type of sentence Yes/No question nouns. The interview result shows the answers given by the students are consistent with the written answers.